Somatic, but not cognitive–affective, symptoms are associated with reduced heart rate variability in individuals with dysphoria - Benvenuti, Simone Messerotti; Buodo, Giulia; Mennella, Rocco; Palomba, Daniela (Frontiers in Psychology, 2015)
Background: Somatic, but not cognitive-affective, symptoms of depression have been associated with reduced heart rate variability (HRV), and with poor prognosis in cardiovascular patients. However, factors concomitant with cardiovascular diseases may confound the relationship between somatic symptoms of depression and reduced HRV. Therefore, this study examined whether reduced HRV was differentially associated with cognitive-affective and somatic symptoms of depression in medically healthy individuals with and without dysphoria. Methods: Self-reported cognitive-affective and somatic symptoms as measured with the Beck Depression Inventory-II (BDI-II) questionnaire and time and frequency domain parameters of HRV were collected in 62 medically healthy individuals, of whom 25 with and 37 without dysphoria. Results: Somatic, but not cognitive-affective, symptoms of depression were inversely associated with standard deviation of NN intervals (SDNN) (beta = -0.476, p < .05), number of interval differences of successive NN intervals greater than 50 ms (NN50) (beta = -0.498, p < .03), and HRV total power (beta = -0.494, p < .04) in the group with dysphoria, after controlling for sex, anxiety and lifestyle factors. Cognitive-affective and somatic symptoms were not related to any of the HRV parameters in the group without dysphoria (all ps > .24). Conclusions: By showing that the relationship between somatic depressive symptoms and reduced HRV extends to medically healthy individuals with dysphoria, the present findings suggest that this association is independent of factors concomitant with cardiovascular diseases. The present study also suggests that individuals with somatic rather than cognitive-affective subsets of depressive symptoms may be at greater risk for developing cardiovascular diseases.